Nutritional condition and starvation in Sardina pilchardus (L.) larvae off southern Portugal compared with some environmental factors - Chícharo, Alexandra (2013)
The aim of this study was to determine the condition and the incidence of starvation among field-caught Sardina pilchardus larvae, using RNA/DNA ratios and to compare them with various abiotic and biotic factors. S. pilchardus larvae were collected off southern Portugal, during April and May 1992. A highly sensitive fluorometric method for quantifying larvae nucleic acid was applied. Sardine larvae were generally in good condition. The means of the RNA/DNA ratios were relatively high and low percentages of starving larvae (RNA/DNA ratio ,1.3) were recorded, ranging from 0 to 12.5%. These two results were associated with high prey availability, which contributes to enhanced condition, and with a high density of potential predators, which may result in fewer larvae in poor condition.